Exposure to cocaine and its main metabolites altered the protein profile of zebrafish embryos. (January 2018) - Parolini, Marco; Bini, Luca; Magni, Stefano; Rizzo, Alessandro; Ghilardi, Anna; Landi, Claudia; Armini, Alessandro; Del Giacco, Luca; Binelli, Andrea
Abstract: Illicit drugs have been identified as emerging aquatic pollutants because of their widespread presence in freshwaters and potential toxicity towards aquatic organisms. Among illicit drug residues, cocaine (COC) and its main metabolites, namely benzoylecgonine (BE) and ecgonine methyl ester (EME), are commonly detected in freshwaters worldwide at concentration that can induce diverse adverse effects to non-target organisms. However, the information of toxicity and mechanisms of action (MoA) of these drugs, mainly of COC metabolites, to aquatic species is still fragmentary and inadequate. Thus, this study was aimed at investigating the toxicity of two concentrations (0.3 and 1.0 μg/L) of COC, BE and EME similar to those found in aquatic ecosystems on zebrafish ( Danio rerio ) embryos at 96 h post fertilization through a functional proteomics approach. Exposure to COC and both its metabolites significantly altered the protein profile of zebrafish embryos, modulating the expression of diverse proteins belonging to different functional classes, including cytoskeleton, eye constituents, lipid transport, lipid and energy metabolism, and stress response. Expression of vitellogenins and crystallins was modulated by COC and both its main metabolites, while only BE and EME altered proteins related to lipid and energy metabolism, as well as to oxidative stress response. Our data confirmed the potential toxicity of low concentrations of COC, BE and EME, and helped to shed light on their MoA on an aquatic vertebrate during early developmental period. Graphical abstract: Highlights: The effects of cocaine and its main metabolites on zebrafish embryo were tested. Tested drugs induced changes in embryo proteome. Vitellogenins and crystallins expression was modulated by all the drugs. Cocaine metabolites affected proteins related to oxidative stress. Environmental concentrations of tested drugs may represent a risk for fish embryos. Abstract : The exposure to environmental concentrations of cocaine and its main metabolites altered the expression of proteins having different functions in zebrafish embryos.